MANAGEMENT ACCOUNTING PRACTICES IN MSMES: A SYSTEMATIC REVIEW OF CROSS-NATIONAL STUDIES - Indriati, Lely; Pratama, Faiz; Aprilia, Citra; Nurhaliza, Iqlima; Dewi, Safina; Dumawan, Christyan; Angelia, Angelia (JRAK, 2025)
The significance of management accounting practices in enhancing the competitiveness and sustainability of micro, small, and medium enterprises (MSMEs) is widely recognised. However, previous research remained fragmented, with limited theoretical integration, methodological diversity, and cross-national perspectives, which restricted a comprehensive understanding of how these practices were studied and applied. This study systematically reviewed developments over the past decade, drawing on open-access articles published in 2015-2025, and applied the PRISMA protocol with bibliometric and thematic analysis. Three major gaps emerged: the limited examination of advanced techniques such as Strategic Management Accounting and Activity-Based Costing, the methodological dominance of single-approach quantitative studies, and the regional concentration of research. The review also highlighted emerging clusters and trends, providing guidance for more context-sensitive studies and practical insights to support MSMEs in driving sustainable economic growth.